2005
DOI: 10.1021/jf051539p
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Quantitation of Phenolic Compounds in New Apricot (Prunus armeniaca L.) Varieties

Abstract: Thirty-seven apricot varieties, including four new releases (Rojo Pasión, Murciana, Selene, and Dorada) obtained from different crosses between apricot varieties and three traditional Spanish cultivars (Currot, Mauricio, and Búlida), were separated according to flesh color into four groups: white, yellow, light orange, and orange (mean hue angles in flesh were 88.1, 85.0, 77.6, and 72.4, respectively). Four phenolic compound groups, procyanidins, hydroxycinnamic acid derivatives, flavonols, and anthocyanins, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
93
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 22 publications
13
93
2
1
Order By: Relevance
“…correspond to flavanone glycosides, followed by flavones, flavonols and the fully polymethoxylated flavones (PMFs) (Ruiz et al, 2005;Nogata et al, 2006;Weber et al, 2006;Mata-Bilbao et al, 2007). Our results were comparable with several latest reports in mandarin and oranges varieties, and our previous studies on the pulp and rind of orange and mandarin species indicated that the Satsume group present the highest amounts of flavanone glycosides, hesperidin and narirutin, compared to the other varieties studied (Cano et al, 2008;Bermejo et al, 2011a,b;Rojas-Argudo et al, 2012).…”
Section: Fruit Quality: Nutritional Qualitymentioning
confidence: 99%
“…correspond to flavanone glycosides, followed by flavones, flavonols and the fully polymethoxylated flavones (PMFs) (Ruiz et al, 2005;Nogata et al, 2006;Weber et al, 2006;Mata-Bilbao et al, 2007). Our results were comparable with several latest reports in mandarin and oranges varieties, and our previous studies on the pulp and rind of orange and mandarin species indicated that the Satsume group present the highest amounts of flavanone glycosides, hesperidin and narirutin, compared to the other varieties studied (Cano et al, 2008;Bermejo et al, 2011a,b;Rojas-Argudo et al, 2012).…”
Section: Fruit Quality: Nutritional Qualitymentioning
confidence: 99%
“…The antioxidant profile of apricot fruit (Prunus armeniaca L.) has recently been analysed with particular reference to the total antioxidant capacity, polyphenols and carotenoids [5][6][7][8][9]. Given that a diverse germplasm exists for this species, the effect of the genotype on antioxidant properties has been considered, and the nutraceutical profiles of many cultivars have been studied in order to find outstanding genotypes rich in antioxidant compounds [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The total antioxidant capacity of this fruit has been measured, especially in the hydrophilic fruit extracts, which mainly contain polyphenols and vitamins. Many phenols have been identified in apricots [8,15,16] that are also known to be a rich source of carotenoids, which are important compounds for the eyes and skin. Recent investigations of the antioxidative effect of carotenes such as phytoene and phytofluene have suggested that they may be part of the oxidative stress defence system in human tissues [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin-3-rutinoside, kaempferol-3-rhamnosyl-hexoside and quercetin-3-acetyl-hexoside were found only in the peel tissue of apricots from different cultivars [187]. Small amounts of kaempferol (27 l 2 lg/kg edible fruit pulp) occur only in the pulp of the cactus pear [191].…”
Section: Structures Of Individual Compounds Content and Changes In Cmentioning
confidence: 95%
“…Plums [131,178], sorghum [88], potatoes [76,124], mangos [124,179,180], kernels [138], cherries [13, 42,43,181], spinach [124,156,182], kale [183], broccoli [124,145], cabbage [55], asparagus [156], lettuces [124], oranges [124], arugulas [137], tea [184], artichokes [132], coffee [185], honey [133,186], apricots [187], citrus fruits [136], oranges [142], bush butter fruits [188], radishes [156,189], cabbages [156,124], pepper [156], olive oil [85,190], cowpeas [104], cactus pears [191], Kancolla seeds [192], Pinto beans [193], beans [82], soybeans [99], and lentils [82].…”
Section: Food Sourcementioning
confidence: 99%